Proses Pengembangan Skill Kewirausahaan Peserta Didik SMP Swasta PAB 10 Medan Estate - Afrida Yanti; Rustam Pakpahan; Afrahul Fadhila Daulai (Jurnal Budi Pekerti Agama Islam, 2024)
This study aims to describe the process of developing entrepreneurial skills of students, about how to plan the development of entrepreneurial skills of students of PAB 10 Medan Estate Private Junior High School, to find out how to implement the development of entrepreneurial skills of students of PAB 10 Medan Estate Private Junior High School, and to find out about the effectiveness of entrepreneurship skill development of PAB 10 Medan Estate Private Junior High School students. This research was conducted with a qualitative approach to obtain data on the planning, implementation and effectiveness of entrepreneurial skill development. The subjects in this study are school principals, teachers and several students at PAB 10 Medan Estate Private Junior High School, with data collection techniques obtained through observation, interviews, and documentation with data analysis techniques used are data reduction, data presentation, and conclusion drawn. The findings of this study show that PAB 10 Medan Estate Private Junior High School in the planning process for developing students' entrepreneurial skills has been carried out well in terms of determining goals and objectives, analyzing previous activities and planning to the preparation of plans for the development of students' entrepreneurial skills. In the implementation of entrepreneurial skill development, all daily activities carried out by students and in all subjects are applied, because the implementation is not only focused on the realm of entrepreneurship, but more on the cultivation of entrepreneurial values. In the evaluation process, it is carried out routinely by the school, both in supervision inside the school and outside the school.